HAID DALAM PERSPEKTIF ISLAM DAN SAINS: Studi tentang Haid Tidak Teratur Pengguna Kontrasepsi - Muttaqin, Khairul (Islamuna: Jurnal Studi Islam, 2019)
Nowadays, there are several contraceptives, such as oral contraceptive pill, contraceptive injection, implants, spiral or IUD (intra uterine device), and IUS (intra uterine system). Some of those have side effects on the irregularity of menstrual period, such as swift menstruation, shorter menstrual period, and longer menstrual period. This issue confuses the concept of Islamic jurisprudence that the maximum menstrual period is fifteen days, whereas it can be more than fifteen days when using contraceptives. This article used library research to analyze menstrual period irregularity as a consequence of contraseptives use based on Islamic and medical literature. This study succesfully revealed that al-Qur’an, hadith, and medical books do not determine the longest menstrual period. Thus, the blood status of women who get menstruation more than fifteen days due to contraceptives use is still menstruation category. [Saat ini, terdapat beberapa alat penunda kehamilan, seperti KB pil, KB suntik, susuk atau implan, spiral atau IUD (intra uterine device), dan IUS (intra uterine system). Sebagian alat ini berefek samping terhadap ketidakteraturan masa haid perempuan; haid bisa keluar secara deras, masa haid lebih singkat, haid bisa keluar lebih lama dari kebiasaan. Problem ini mengacaukan konsep fikih bahwa masa haid perempuan paling lama adalah 15 hari, padahal masa haid bisa lebih dari 15 hari bila menggunakan alat penunda kehamilan. Dengan kajian pustaka, artikel ini menganalisis masa haid yang tidak teratur akibat penggunaan alat penunda kehamilan berdasarkan teks-teks dasar Islam dan medis. Artikel ini berhasil mengungkap bahwa al-Qur’an, hadis, dan medis tidak menentukan masa haid terlama, sehingga status darah yang keluar dari perempuan yang haid lebih dari 15 hari akibat penggunaan alat kontrasepsi adalah haid]